Valerian essential oil for treating insomnia via the serotonergic synapse pathway - Wang, Wenfei; Wang, Yichun; Guo, Qiuting; Li, Huiting; Wang, Zhaoqiang; Li, Jia; Li, Taotao; Tang, Tiantian; Wang, Yujiao; Jia, Yanzhuo; Wang, Yao; Zou, Junbo; et al. (Frontiers in Nutrition, 2022)
Valerian volatile oil can be used in the treatment of insomnia; however, the active components and mechanisms of action are currently unclear. Therefore, we used transcriptome sequencing and weight coefficient network pharmacology to predict the effective components and mechanism of action of valerian volatile oil in an insomnia model induced by intraperitoneal injection of para-Chlorophenylalanine (P C P A) in SD rats. Valerian essential oil was given orally for treatment and the contents of 5-hydroxytryptamine receptor 1A (5-HT 1 A R), γ-aminobutyric acid (GABA), cyclic adenosine monophosphate (cAMP), and protein kinase A (P K A) in the hippocampus of rats in each group were detected by enzyme-linked immunosorbent assay (ELISA), western blot, Polymerase Chain Reaction (PCR), and immunohistochemistry. The results showed that after treatment with valerian essential oil, insomnia rats showed significantly prolonged sleep duration and alleviated insomnia-induced tension and anxiety. Regarding the mechanism of action, we believe that caryophyllene in valerian essential oil upregulates the 5-HT 1 A R receptor to improve the activity or affinity of the central transmitter 5-HT, increase the release of 5-HT, couple 5-HT with a G protein coupled receptor, convert Adenosine triphosphate (ATP)into cAMP (catalyzed by A D C Y 5), and then directly regulate the downstream pathway. Following pathway activation, we propose that the core gene protein kinase P K A activates the serotonergic synapse signal pathway to increase the expression of 5-HT and GABA, ultimately improving insomnia symptoms and alleviating anxiety. This study provides a theoretical basis for the application of valerian volatile oil in health food.